2001
DOI: 10.1029/2000pa000547
|View full text |Cite
|
Sign up to set email alerts
|

Empirical relationship between pH and the boron isotopic composition of Globigerinoides sacculifer: Implications for the boron isotope paleo‐pH proxy

Abstract: Abstract. Culture experiments were carried out with the planktonic foraminifera Globigerinoides sacculifer at three different pH values (7.6+0.05, 8.20+0.05, and 8.60+0.05) in order to establish the pH dependence of the boron isotopic fractionation between the calcitic tests of G. sacculifer and seawater. Additional objectives were to compare the pH dependences of boron isotopic composition of G. sacculifer with that of Orbulina universa and inorganic calcite in order to evaluate the robustness of the boron is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(151 citation statements)
references
References 20 publications
8
143
0
Order By: Relevance
“…Several studies have shown that the boron isotopic composition is controlled by pH [10,58,73,74]. According to Palmer et al [75], pH can restrict the boron isotopic characteristics of a water body to a certain extent.…”
Section: The Influence Of Ph On B Isotopesmentioning
confidence: 99%
“…Several studies have shown that the boron isotopic composition is controlled by pH [10,58,73,74]. According to Palmer et al [75], pH can restrict the boron isotopic characteristics of a water body to a certain extent.…”
Section: The Influence Of Ph On B Isotopesmentioning
confidence: 99%
“…For example, prior studies have shown that for a given pH SW , δ 11 B CaCO 3 of the coral species Porites cylindrica and Acropora nobilis are moderately elevated relative to δ 11 B CaCO 3 of the foraminifera Globigerinoides sacculifer and substantially elevated relative to δ 11 B CaCO 3 of the mussel Mytilus edulis ( Fig. 2; Heinemann et al, 2012;Sanyal et al, 2001). One possible explanation for these differences is that corals are maintaining their calcifying fluids at higher pH than the calcifying fluids of foraminifera, which are in turn elevated relative to the pH CF of mussels.…”
Section: The Role Of Calcification Site Ph In Calcareous Biomineralizmentioning
confidence: 99%
“…Although early studies assumed that δ 11 B CaCO 3 was indeed equivalent to seawater δ 11 B B(OH) 4 − (e.g., Hemming and Hanson, 1992), Sanyal et al (2000Sanyal et al ( , 2001 observed that empirically derived δ 11 B CaCO 3 -pH curves of biogenic and abiogenic calcites were parallel but vertically offset from the theoretical δ 11 B B(OH) − 4 -pH curve, which led them to conclude that paleo-seawater pH cannot always be directly calculated from δ 11 B CaCO 3 using the theoretical δ 11 B B(OH) − 4 -pH relationship (i.e., δ 11 B CaCO 3 -pH relationships must be empirically calibrated for the species hosting the paleo-pH proxy).…”
Section: In Modern Seawater B(oh)mentioning
confidence: 99%
See 1 more Smart Citation
“…Nägler et al, 2000) preserved in foraminiferal test carbonate have also been used to reconstruct sea water temperature. Other geochemical proxies useful in environmental reconstructions include B isotopes, which are used to determine pH changes in the ocean water (Sanyal et al, 2001;Yu et al, 2007), and Cd, which is a proxy for nutrient concentrations (Boyle, 1988;Rickaby and Elderfield, 1999;Martin and Lea, 1998).…”
Section: Introductionmentioning
confidence: 99%